EVALUASI STRATEGI DOTS (DIRECTLY OBSERVED TREATMENT SHORT COURSE) DI PUSKESMAS TLOGOMULYO KABUPATEN TEMANGGUNG TAHUN 2021 - Riza Rahayuning Widya; Chatila Maharani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Tubercolosis (TB) is a chronic infectious disease caused by infection of Mycobacterium Tuberculosis. The new case finding rate at Puskesmas Tlogomulyo in 2021 was 9.5% (<70%). Meanwhile, the treatment success rate in 2021 was 75% (<90%). WHO declared TB as a global health emergency and recommended DOTS (Directly Observed Treatment Short Course) as a TB disease control strategy. This research aimed to determine the evaluation of the DOTS strategy at Puskesmas Tlogomulyo in 2021.This study used descriptive qualitative method and used purposive sampling for selecting the informants. The main informants were Head of Health Center (Puskesmas), General Practitioners, Head of TB Program, Laboratory Officers, Pharmacists Assistants. While, triangulation informants were TB Patients, (Pengawas Menelan Obat-PMO), and Head of TB Program in Health Office. Data were collected with interviews, observation, documentation, and secondary data. In terms of context, Puskesmas was not succeeded. For the input, DOTS training was not implemented, there was not have a legal decree for the DOTS team, while the funds, infrastructure and procedures were fulfilled. Aspect of the process were diagnosis, OAT, SITB, but for PMO it was not optimal. In terms of products, the problem with the case finding rate and the success of treatment because pandemic and side effects. Suggestions for puskesmas to improve program innovation for the DOTS strategy till achievement the indicator number achieved were choose the appropriate PMO and further increase community knowledge through Puskesmas Pembantu (Pustu) and Pos Binaan Terpadu (Posbindu).